Pengembangan Kecerdasan Emosional Bagi Siswa Kelas Awal Madrasah Ibtidaiyyah Pada Pembelajaran Bahasa Indonesia - Rozib Sulistiyo (Universitas Cokroaminoto Yogyakarta, 2017)
In order to reinforce the importance of emotional development students in the early MI class were studied in the literature about the use of story methods in learning Indonesian language. Some attitudes and behaviors can be developed in strengthening the EQ of early grade MI students. For this reason, teachers are advised to use the surrounding environment as a learning media that is contextual during their stories on Indonesian language subjects.